FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PENYELENGGARAAN PEMBANGUNAN DI DESA LOA KULU KOTA KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Rudiansyah . (Jurnal Paradigma (JP), 2017)
The purpose of this research is to explain about execution of rural parliamentary function of Loa Kulu Kota. The result of study show that in doing its function, such as legislation, budgeting, supervision and protecting social custom, rural parliarmentary  of Loa Kulu Kota did not too optimal due to several factors.